Behavior of wood during the thermal transition between torrefaction and pyrolysis: chemical and physical modifications. Issue 1 (2nd January 2023) - Colin, Baptiste; Quirino, Rafael L.; Ntsika-Mbou, Christ Y.; Lin, Yu-Ying; Lin, Bo-Jhih; Leconte, François; Petrissans, Anelie; Chen, Wei-Hsin; Petrissans, Mathieu
ABSTRACT : Despite the wealth of physical and chemical information available about wood torrefaction and pyrolysis, very few studies to date have focused on the transition between these two processes. It has been experimentally determined, however, that torrefaction and pyrolysis lead to very different products, indicating a change in their degradation chemistry. There exists, therefore, a need to investigate this transition between torrefaction and pyrolysis from a chemical perspective, very useful for the development of kinetic models. This study focuses on investigating thermogravimetric analysis, shrinkage, flexural strength, total weight loss, of two common industrial European wood species treated at temperatures ranging from 250°C to 400°C. A comparison reveals an obvious change in the degradation of cellulose as a function of treatment temperature that can be correlated with the yield of the main thermal treatment products, such as acetic acid, furfural, CO, H2, etc. At temperatures higher than 350°C, all wood components are extensively degraded. In conclusion, this study indicates a deep modification during the transition between torrefaction and pyrolysis. The results obtained in this study help establish specific temperature ranges, based on wood component degradation, that can be used in the refinement of kinetic models for wood thermal treatment. It is envisioned that, due to the sudden change in behavior at temperatures covering a range between torrefaction and soft pyrolysis, an adequate model with distinct stages is required. Ultimately, this study aims at defining, based on TGA, DTG, mechanical testing, color/appearance, and dimensional change results, the appropriate temperature ranges to be used in the refinement of unique kinetic models that contemplate the degradation of wood components.